The construction of walkway slab for MRT Station at Kepong, Kuala Lumpur / Amreel Zulfiqar Muhammad Taslim - Muhammad Taslim, Amreel Zulfiqar (2021)
Walkway slab is a walkway that has been formed by using concrete and generally contains steel reinforcement either by rebar or steel fiber and also can be formed in situ or prefabricated. Usually walkway slab is around 50mm-60mm minimum thick but they also can reach until 70mm thick depending on the surrounding and reinforcement. There are two ways of construct the walkway slab which is precast and in situ depending on suitability. However, this report will discuss the construction of walkway slab for MRT Station at Kepong, Kuala Lumpur. The objectives of this report are mainly focused on the method of construction of concrete walkway slab and machineries and tools that needed to construct the concrete walkway slab, and lastly identifying the advantages and disadvantages of concrete walkway slab. There are 5 stages of constructing in situ walkway slab that starts from backfilling and end up with finishing. Data and information was collected through observation on site, research from document contract and interview with the person that in-charge in that construction. Method that used during construction work was necessary as it defined the efficiency of the working progress of the construction.